The Effect Of Using English Song As A Media Towards Students Speaking Ability In SMA Tamansiswa Pematangsiantar (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
The topic of this study is the effect of Using English Song as a media towards Students speaking ability, an action research of the eleventh grade students of SMA Tamansiswa Pematangsiantar in the academic year 2023/2024. In this study, the writer limited the discussion by stating the following problem: Does any effect of English song as a media toward students’ speaking ability? The objective of this study was to know whether using English song is effective or not as a media towards student’s speaking ability. Action research approach was adopted in this study. The population of the study was eleventh grade students of SMA Tamansiswa  Pematangsiantar in the academic year of 2023/2024. The writer took the whole students of XI MIPA 2 as the subject of the research. There were 35 students. It was conducted on 6th until 15th of March 2024. The techniques used for obtaining data were collecting data from the students by using speaking test. In the first activity, the writer gave a pre-test in order to find out the student’s creativity in writing descriptive text. The second activity, the writer gave a treatment where the writer gave and explained the material of descriptive text to students. In the last activity, the students were given a post-test. The result of the students’ progress during the teaching and learning process by the effect of using English song as a media was good. The students’ achievement increased from the second meeting to the last. The students’ mean value in pre-test was 50,06. Then in post-test increased to become 74,60 of students passed the Minimum Mastery Criterion with the mean score result was 19,69. In conclusion, the researcher found that the students improved their comprehension in English song lyric, they could speaking song lyric, and produce English song with the various and diverse idea